2020 Constitutional Reform as the Problem of Legitimacy Theory - A. N. Medushevskiy (Теоретическая и прикладная юриспруденция)
The legitimacy is one of the key resources of stability for all political regimes but its importance growing still much in regimes under transformation. The general legitimacy theory exposes why and how the dominant political class disposes the trust of society to stay in power by using available symbolic, moral and legal resources of self-legitimization. In contemporary law-based state the ground of the legitimacy is normally associated with the national constitution – its fundamental values, principles and norms as well as with general public agreement on mode of their application by government institutions and officials. Thus, each important constitutional revision means both the challenge to the established legitimacy and an attempt to reconstruct it in new forms. The author analyses the impact of Russian 2020 constitutional reform in the transformation of the Russian political regime legitimacy. He exposes the reciprocal interconnections between legitimacy and constitutionalism, regarding such items as positive and negative law-making impulses; substantive and instrumental aspects of reform; national, regional and local dimensions; constitutional and meta-constitutional parameters of the legitimization process as well as declared and undeclared reasons, motives, arguments and political technologies of amending process. According his conclusion, the main result of the Russian constitutional reform consists in the reconstructed legitimacy formula as a legal ground for consolidation of power under transition process and a fresh start for the new form of constitutional authoritarianism.